Perlindungan Hukum Terhadap Partisipasi Masyarakat (Anti SLAPP) Dalam Penegakan Hukum Lingkungan Hidup di Indonesia - Indrawati, Nani (Media Iuris, 2022)
Abstract Anti SLAPP is a new terminology that was first recognized in the United States in 1996. Basically, Anti-SLAPP is a legal policy that provides legal protection for people who fight for the public interest's purposes acknowledged in constitutional and statutory provisions. In Indonesia, the provisions which are similar to Anti-SLAPP in the environmental area (anti-eco SLAPP) is included in Article 66 of the Law on Environmental Protection and Management (LEPM) which intends to protect environmental defenders from criminal charges and lawsuits for exposing environmental rights violation. Law enforcers, especially judges, are still having difficulty in detecting cases that are indicated as SLAPP and stop the case to continue in the early stage. Article 66 of the LEPM are a symbol of legal protection, as well as a manifestation of the accommodative attitude of the LEPM towards the importance of environmental public participation including protecting individuals and groups who fight for the environmental rights against criminal charges and civil litigation. The lack of provisions on the procedures and mechanisms of the Anti-SLAPP makes it difficult to implement Article 66 of the LEPM. Consequently, law enforcers particularly court judges apply and interpret Article 66 of LEPM is not in line with the original intention of Anti SLAPP's provision. Keywords: Anti-SLAPP; Public Participation; Environmental Law Enforcement. Abstrak Anti-SLAPP merupakan terminologi baru yang dikenal pertama kali di Amerika Serikat pada tahun 1996. Pada intinya Anti-SLAPP adalah ketentuan yang memberikan perlindungan hukum terhadap masyarakat yang memperjuangkan kepentingan publik yang diakui dalam konstitusi dan perundang-undangan. Di Indonesia, ketentuan serupa dengan Anti-SLAPP dibidang lingkungan hidup (anti-eco SLAPP) termuat dalam Pasal 66 Undang-Undang tentang Perlindungan dan Pengelolaan Lingkungan Hidup (UU PPLH) yang dimaksudkan untuk melindungi para pembela lingkungan hidup dari tuntutan pidana dan gugatan perdata karena mengungkap pelanggaran hak atas lingkungan hidup. Para penegak hukum khususnya hakim masih mengalami kesulitan mendeteksi kasus yang terindikasi SLAPP dan menghentikan kasus pada tahap awal. Ketentuan Pasal 66 UU PPLH merupakan simbol perlindungan hukum, sekaligus sebagai wujud dari sikap akomodatif UU PPLH terhadap pentingnya peran serta masyarakat, termasuk melindungi individu dan kelompok masyarakat yang memperjuangkan hak atas lingkungan hidup dari tuntutan pidana dan gugatan perdata. Ketiadaan ketentuan tentang prosedur dan mekanisme Anti-SLAPP menyulitkan implementasi Pasal 66 UU PPLH. Akibatnya, para penegak hukum khususnya hakim dalam menerapkan dan menafsirkan Pasal 66 UU PPLH berbeda dengan tujuan awal ketentuan Anti SLAPP. Kata Kunci: Anti-SLAPP; Partisipasi Masyarakat; Penegakan Hukum Lingkungan Hidup.